Dissemination and characteristics of carbapenem-resistant Klebsiella pneumoniae in nine district hospitals in southwestern China - Wang, Yonghong; Ouyang, Yan; Xu, Xiuyu; Sun, Shan; Tian, Xiaolang; Liu, Hang; Xia, Yun (Frontiers in Microbiology, 2023)
Background Carbapenem-resistant Klebsiella pneumoniae (CRKP) is epidemically transmitted globally, but few studies focused on the prevalence in district-level hospitals. In this study, we investigated CRKP strains collected from nine district hospitals from September 2019 to September 2020, aiming to determine the resistance mechanisms, virulence profiles, and molecular epidemiological characteristics of CRKP in district hospitals in Southwest China. Methods A total of 51 CRKP strains were collected from 9 district-level hospitals. Matrix-assisted laser desorption/ionization-time of flight mass spectrometer was used for strain identification review, and the micro-broth dilution method was used for antibiotic sensitivity detection. Molecular epidemiological investigation of strains was performed by multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) methods. PCR and efflux pump inhibition tests were used to detect CRKP resistance mechanisms. PCR and serum killing tests were used to detect capsular serotype, virulence-related genes, and virulence validation. Results The CRKP strains in district hospitals presented high levels of MIC50 and MIC90 in carbapenem antibiotics especially ertapenem and meropenem. A total of 90.2% (46/51) CRKP strains were detected as carbapenemase producers, and the proportion of strains co-expressing carbapenemases was 11.8% (6/51). All CRKP strains were grouped into eight MLST types, and ST11 was the most prevalent genotype. A total of 11.8% (6/51) CRKP isolates were positive for the string test, and three strains of hypervirulent and carbapenem-resistant K. pneumoniae (HV-CRKP) were positive in serum killing test. The molecular typing of all the CRKP isolates was grouped into 29 different PFGE patterns, and 40 ST11 isolates belonged to 20 different PFGE clusters. Conclusion CRKP strains showed high-level antibiotic resistance and virulence phenotype in district hospitals in Southwest China, which suggested that we should immediately pay attention to the rapid dissemination of the CRKP in regional hospitals. Our study will provide new insights into the epidemiology of CRKP in regional hospitals, which will help regional hospitals develop nosocomial infection prevention and control policies tailored to local conditions.